The MIREN Road Survey Database: Standardized Vegetation Sampling to Advance Our Understanding of Biodiversity Responses in Mountain Systems Across the Globe - Sylvia Haider; Jonas J. Lembrechts; Jake Alexander; Vincent Ralph Clark; Lisa J. Rew; Meike Buhaly; Marc Achermann; Alla Aleksanyan; Alisa Alvarez; Marco Andrello; José R. Arévalo; Valeria Aschero; et al. (Global Ecology and Biogeography, 2026)
Motivation The database initiated by the Mountain Invasion Research Network (MIREN) is one of the few globally implemented standardized vegetation surveys in mountains. The focus is on collecting plant species occurrences at 5‐year intervals along and adjacent to mountain roads spanning elevational gradients, with the goal of providing critical information about the ongoing spread of non‐native plants and the potential impacts of climate and human‐caused disturbance in the form of road infrastructure on mountain vegetation. Main Types of Variables Contained To date, the database contains almost 170,000 georeferenced records of plant species. Overall, 6854 vascular plant species were observed in 3364 plots across 25 regions, with many of these plots being revisited every 5 years. Each plot is identified by its coordinates, elevation and distance to the road. The status of each individual species (native, non‐native or unknown) is determined in accordance with regional databases. Spatial Location and Grain Plant species were surveyed at 20 sample sites, placed at regular elevational intervals along each mountain road, with typically three roads selected per region. Each sample site is subdivided into three 2 m × 50 m plots, one parallel to the road and two perpendicular to it, extending into adjacent vegetation. The 25 studied regions cover all continents except Antarctica. Time Period and Grain Data were collected between 2007 and 2023, with surveys being repeated at 5‐year intervals in a subset of regions. Three regions include four time‐steps, while seven and three regions were sampled three times or twice, respectively. In most regions, long‐term monitoring is ongoing. Major Taxa and Level of Measurement All vascular plant species. Software Format Data are available through a .csv file on Zenodo ( https://doi.org/10.5281/zenodo.15749536 ).

Collaborating across mountains: contributions of the Mountain Invasion Research Network (MIREN) to ecology and conservation - Aníbal Pauchard; Eduardo Fuentes-Lillo; Jake Alexander; Manzoor A. Shah; Agustina Barros; Lohengrin Cavieres; Sylvia Haider; Jonas J. Lembrechts; Keith McDougall; John W. Morgan; Vincent Ralph Clark; Irfan Rashid; et al. (Biological Invasions, 2026)

Global Homogenisation of Plant Communities Along Mountain Roads by Non‐Native Species Despite Mixed Effects at Smaller Scales - Meike Buhaly; Jake M. Alexander; Aníbal Pauchard; Lisa J. Rew; Tim Seipel; José Ramón Arévalo; Valeria Aschero; Joshua P. Averett; Agustina Barros; Lohengrin A. Cavieres; V. Ralph Clark; Curtis C. Daehler; et al. (Global Ecology and Biogeography, 2025)
Aim Mountain ecosystems are experiencing increased invasion of non‐native plants. These increases in non‐native species put mountains at risk of biotic homogenisation and a reduction of biodiversity. Our study aims to test if non‐native plant species are contributing to biotic homogenisation along roadways in mountain regions and how this changes along elevation gradients and across spatial scales. Location 18 globally distributed mountain regions. Time Period 2012–2023. Major Taxa Studied Vascular plants. Methods We used standardised vegetation surveys including species cover from 18 mountain regions worldwide to analyse whether the addition of non‐native species to the native flora increased or decreased Bray–Curtis dissimilarity (i.e., beta‐diversity) among roadside plant communities along elevation gradients ranging from 15 to 3919 m a.s.l. We tested this at the local, regional, continental and global scales using mixed‐effects models and confirmed it using null models. Results In the New World, we mainly observed homogenisation across regions and scales, as beta‐diversity was mostly lower with the addition of non‐native species. This was particularly true for low elevations. In contrast, we predominantly found community differentiation in the Old World, specifically at smaller (i.e., local and regional) scales. At the global scale, communities became more similar through the addition of non‐native species at all elevations. Main Conclusions Large‐scale homogenisation might be interpreted as a signal that high‐elevation plant communities along roadways may become more similar as non‐native species continue to spread upwards. Future studies should investigate the mechanisms driving the observed patterns of both homogenisation and differentiation by non‐native species, and explore the potential consequences of these patterns for ecosystem function and resilience.

Beyond the Trail—Understanding Non‐Native Plant Invasions in Mountain Ecosystems - Agustina Barros; Eduardo Fuentes Lillo; Valeria Aschero; Aníbal Pauchard; María Alisa Alvarez; Ronja Wedegärtner; Jan Clavel; Jana Müllerová; Jan Pergl; Shengwei Zong; Michaela Vítková; Tereza Klinerová; et al. (Global Ecology and Biogeography, 2025)
Aim We aimed to examine the abiotic, biotic and anthropogenic drivers of non‐native plant species distribution along hiking trails in mountainous regions. Location Nine mountain regions across six continents, including North America (USA), South America (Argentina and Chile), Europe (Sweden, Norway, Czech Republic), Africa (South Africa), Asia (China) and Oceania (Australia). Time Period Data were collected between 2016 to 2022 during the summer season. Major Taxa Studied Vascular plants. Methods We implemented a standardised sampling design (MIREN trail survey) with T‐shaped sample sites placed parallel to trails and perpendicular to adjacent vegetation. We examined the main drivers (abiotic, biotic and anthropogenic factors) affecting non‐native species' presence, richness and cover. Results At the global scale, abiotic (climatic) variables explained most of the variation in non‐native species richness. In contrast, biotic factors were the most important for the presence and cover of non‐native plants. Anthropogenic factors, including distance to the trail, use intensity and livestock grazing, were also important but to a lesser extent than the main factors. While the total number of non‐native species differed across regions, the patterns explaining plant invasions were consistent. Main Conclusions Our regional study identified mountain trails that are particularly vulnerable to plant invasions. Our findings suggest that under future scenarios of climate change, increased anthropogenic pressure and heightened livestock activity, the presence of non‐native species beyond trail edges may become more frequent. This highlights the need to restrict off‐trail activities in areas of high conservation value.

Climate change and more disturbed land-use types will further the invasion of a non-native annual grass, Ventenata dubia - Arjun Adhikari; Jane Mangold; Kumar P. Mainali; Lisa J. Rew (Biological Invasions, 2023)
Identification of suitable habitat for invasive weeds and their projected infestation extent across different land use cover types under a changing climate is crucial for the broad management goals of prevention, detection, and rapid response. In this study, we adopted an ensemble approach of species distribution models to project potential habitat of the invasive annual grass, Ventenata dubia , within the Gallatin County and along its road corridors, in Montana, USA, under current and future climates. The model prediction of V. dubia habitat was excellent with an AUC value of > 0.90. The climate predictors with most influence on V . dubia occurrence were precipitation, potential evapo-transpiration, relative humidity, vapor pressure deficit, and solar radiation for growing season months. Under current climate, the model projected 243 and 1,371 km 2 coverage of V. dubia along road corridors and the entire County, respectively. The projected coverage of V. dubia was greatest for road corridors (239% under RCP4.5 and 302% under RCP8.5) compared to that of Gallatin County (127% under RCP4.5 and 241% under RCP8.5). Among the land use cover types, the model projected greatest expansion of V. dubia across agriculture land with 425% and 484%, and grasslands with 278% and 442% under RCP4.5 and RCP8.5 respectively. Our modelling approach suggests that the changing climate will facilitate spread and establishment of non-native species in disturbed habitats. We conclude that V. dubia with a short history of invasion is expanding at an alarming rate and requires greater investment in detection and monitoring to prevent further expansion.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Correction to: Future distribution of invasive weed species across the major road network in the state of Montana, USA - Arjun Adhikari; Lisa J. Rew; Kumar P. Mainali; Subodh Adhikari; Bruce D. Maxwell (Regional Environmental Change, 2020)

Future distribution of invasive weed species across the major road network in the state of Montana, USA - Arjun Adhikari; Lisa J. Rew; Kumar P. Mainali; Subodh Adhikari; Bruce D. Maxwell (Regional Environmental Change, 2020)
Invasive plant species are a significant global problem, with the potential to alter structure and function of ecosystems and cause economic damage to managed landscapes. An effective course of action to reduce the spread of invasive plant species is to identify potential habitat incorporating changing climate scenarios. In this study, we used a suite of species distribution models (SDMs) to project habitat suitability of the eleven most abundant invasive weed species across road networks of Montana, USA, under current (2005) conditions and future (2040) projected climates. We found high agreement between different model predictions for most species. Among the environmental predictors, February minimum temperature, monthly precipitation, solar radiation, and December vapor pressure deficit accounted for the most variation in projecting habitat suitability for most of the invasive weed species. The model projected that habitat suitability along roadsides would expand for seven species ranging from + 5 to + 647% and decline for four species ranging from − 11 to − 88% under high representative concentration pathway (RCP 8.5) greenhouse gas (GHG) trajectory. When compared with current distribution, the ensemble model projected the highest expansion habitat suitability with six-fold increase for St. John’s Wort ( Hypericum perforatum ), whereas habitat suitability of leafy spurge ( Euphorbia esula ) was reduced by − 88%. Our study highlights the roadside areas that are currently most invaded by our eleven target species across 55 counties of Montana, and how this will change with climate. We conclude that the projected range shift of invasive weeds challenges the status quo, and requires greater investment in detection and monitoring to prevent expansion. Though our study focuses across road networks of a specific region, we expect our approach will be globally applicable as the predictions reflect fundamental ecological processes.

Running off the road: roadside non-native plants invading mountain vegetation - Keith L. McDougall; Jonas Lembrechts; Lisa J. Rew; Sylvia Haider; Lohengrin A. Cavieres; Christoph Kueffer; Ann Milbau; Bridgett J. Naylor; Martin A. Nuñez; Anibal Pauchard; Tim Seipel; Karina L. Speziale; et al. (Biological Invasions, 2018)

Mountain roads and non‐native species modify elevational patterns of plant diversity - Sylvia Haider; Christoph Kueffer; Helge Bruelheide; Tim Seipel; Jake M. Alexander; Lisa J. Rew; José Ramón Arévalo; Lohengrin A. Cavieres; Keith L. McDougall; Ann Milbau; Bridgett J. Naylor; Karina Speziale; et al. (Global Ecology and Biogeography, 2018)
Aim We investigated patterns of species richness and community dissimilarity along elevation gradients using globally replicated, standardized surveys of vascular plants. We asked how these patterns of diversity are influenced by anthropogenic pressures (road construction and non‐native species). Location Global. Time period 2008–2015. Major taxa studied Vascular plants. Methods Native and non‐native vascular plant species were recorded in 943 plots along 25 elevation gradients, in nine mountain regions, on four continents. Sampling took place in plots along and away from roads. We analysed the effects of elevation and distance from road on species richness patterns and community dissimilarity (beta‐diversity), and assessed how non‐native species modified such elevational diversity patterns. Results Globally, native and total species richness showed a unimodal relationship with elevation that peaked at lower‐mid elevations, but these patterns were altered along roads and due to non‐native species. Differences in elevational species richness patterns between regions disappeared along roadsides, and non‐native species changed the patterns’ character in all study regions. Community dissimilarity was reduced along roadsides and through non‐native species. We also found a significant elevational decay of beta‐diversity, which however was not affected by roads or non‐native species. Main conclusions Idiosyncratic native species richness patterns in plots away from roads implicate region‐specific mechanisms underlying these patterns. However, along roadsides a clearer elevational signal emerged and species richness mostly peaked at mid‐elevations. We conclude that both roads and non‐native species lead to a homogenization of species richness patterns and plant communities in mountains.

Competition between cheatgrass and bluebunch wheatgrass is altered by temperature, resource availability, and atmospheric CO2 concentration - Christian D. Larson; Erik A. Lehnhoff; Chance Noffsinger; Lisa J. Rew (Oecologia, 2018)

Lags in the response of mountain plant communities to climate change - Jake M. Alexander; Loïc Chalmandrier; Jonathan Lenoir; Treena I. Burgess; Franz Essl; Sylvia Haider; Christoph Kueffer; Keith McDougall; Ann Milbau; Martin A. Nuñez; Aníbal Pauchard; Wolfgang Rabitsch; et al. (Global Change Biology, 2018)
Rapid climatic changes and increasing human influence at high elevations around the world will have profound impacts on mountain biodiversity. However, forecasts from statistical models (e.g. species distribution models) rarely consider that plant community changes could substantially lag behind climatic changes, hindering our ability to make temporally realistic projections for the coming century. Indeed, the magnitudes of lags, and the relative importance of the different factors giving rise to them, remain poorly understood. We review evidence for three types of lag: “dispersal lags” affecting plant species’ spread along elevational gradients, “establishment lags” following their arrival in recipient communities, and “extinction lags” of resident species. Variation in lags is explained by variation among species in physiological and demographic responses, by effects of altered biotic interactions, and by aspects of the physical environment. Of these, altered biotic interactions could contribute substantially to establishment and extinction lags, yet impacts of biotic interactions on range dynamics are poorly understood. We develop a mechanistic community model to illustrate how species turnover in future communities might lag behind simple expectations based on species’ range shifts with unlimited dispersal. The model shows a combined contribution of altered biotic interactions and dispersal lags to plant community turnover along an elevational gradient following climate warming. Our review and simulation support the view that accounting for disequilibrium range dynamics will be essential for realistic forecasts of patterns of biodiversity under climate change, with implications for the conservation of mountain species and the ecosystem functions they provide.

A warmer and drier climate in the northern sagebrush biome does not promote cheatgrass invasion or change its response to fire - Christian D. Larson; Erik A. Lehnhoff; Lisa J. Rew (Oecologia, 2017)

Plant invasions into mountains and alpine ecosystems: current status and future challenges - Jake M. Alexander; Jonas J. Lembrechts; Lohengrin A. Cavieres; Curtis Daehler; Sylvia Haider; Christoph Kueffer; Gang Liu; Keith McDougall; Ann Milbau; Aníbal Pauchard; Lisa J. Rew; Tim Seipel (Alpine Botany, 2016)

Drivers of Bromus tectorum Abundance in the Western North American Sagebrush Steppe - Tyler J. Brummer; Kimberley T. Taylor; Jay Rotella; Bruce D. Maxwell; Lisa J. Rew; Matt Lavin (Ecosystems, 2016)

Non-native and native organisms moving into high elevation and high latitude ecosystems in an era of climate change: new challenges for ecology and conservation - Aníbal Pauchard; Ann Milbau; Ann Albihn; Jake Alexander; Treena Burgess; Curtis Daehler; Göran Englund; Franz Essl; Birgitta Evengård; Gregory B. Greenwood; Sylvia Haider; Jonathan Lenoir; et al. (Biological Invasions, 2016)

Drivers of plant invasion vary globally: evidence from pine invasions within six ecoregions - Kimberley T. Taylor; Bruce D. Maxwell; Aníbal Pauchard; Martin A. Nuñez; Duane A. Peltzer; André Terwei; Lisa J. Rew (Global Ecology and Biogeography, 2016)
Aim To determine biotic and abiotic controls on pine invasion globally within six ecoregions that include both introduced and native ranges. Locations R ío N egro province, A rgentina; A ysén and A raucanía regions, C hile; S outh I sland (two ecoregions), N ew Z ealand; G reater Y ellowstone ecosystem, USA . Methods We quantified tree abundance and size across invasion fronts of the widespread invasive tree species P inus contorta at each of the nine sites, encompassing both the native and introduced range. We also determined the relative importance of propagule pressure, abiotic characteristics and biotic factors for invasion success. Finally, key plant population metrics such as individual tree growth rates and reproductive effort were compared between native and introduced ranges. Results P inus contorta density decreased with increasing distance from source population in all cases, but the importance and shape of this relationship differed among sites due, primarily to biotic factors. For example, areas dominated by native southern beech forest ( F uscospora cliffortioides or N othofagus spp.) were not invaded, and this biotic resistance was not overcome by high propagule pressure. In contrast, shrublands were more highly invaded than grasslands, contradicting previous generalizations about pine invasions. P inus contorta growth was faster, age to maturity was earlier and reproductive effort was higher in the introduced ranges compared with the native range, suggesting a demographic shift towards more rapid population growth in introduced regions. Climatic differences between the ranges may explain, at least in part, the observed pattern. Main conclusions We demonstrate that although biological invasions are driven by propagule pressure across different ecoregions, these processes interact strongly with biotic factors. Intriguingly, our results suggest that propagule pressure may become less important than biotic interactions as invasions proceed. Multi‐region studies including both the native and introduced ranges provide unparalleled opportunities for understanding how these interactions change among regions as invasions proceed.

A probabilistic Bayesian framework for progressively updating site-specific recommendations - Patrick G. Lawrence; Lisa J. Rew; Bruce D. Maxwell (Precision Agriculture, 2015)

Performance of the herb Verbascum thapsus along environmental gradients in its native and non‐native ranges - Tim Seipel; Jake M. Alexander; Curtis C. Daehler; Lisa J. Rew; Peter J. Edwards; Pervaiz A. Dar; Keith McDougall; Bridgett Naylor; Catherine Parks; Fredric W. Pollnac; Zafar A. Reshi; Mel Schroder; et al. (Journal of Biogeography, 2015)
Aim We evaluated whether the performance of individuals and populations of the invasive plant Verbascum thapsus differs between its native and non‐native ranges, across climate gradients, and in response to its position in a global‐scaled niche model. Location India (Kashmir) and Switzerland (native range) and Australia and USA (Hawaii, Montana and Oregon) (non‐native range). Methods We measured population characteristics (density of flowering individuals, population size), plant traits (plant height, number of flowering branches) and seed germination for 50 populations of V. thapsus growing along elevational gradients in six mountain regions around the world (two in the native range, and four in the non‐native range). We fitted linear regression models to determine the relationship of plant and population level performance variables to range, region, climate and probability of occurrence from a global niche model. Results Plant height, number of flowering branches and population density of V. thapsus did not differ consistently between the native and non‐native ranges, but the area covered by populations in the non‐native range was on average two orders of magnitude larger than the area of native populations. Within and among regions, individual plant performance traits responded variably to precipitation and mean annual temperature, depending on the climatic range of the observed populations; however, performance was greater for populations that had a greater modelled probability of occurrence. Seed germination under controlled conditions was highest between 20 and 35 °C and consistent across populations, although germination at low temperatures was substantially higher for native populations from Kashmir. Main conclusions The introduction of V. thapsus to its non‐native range is not associated with consistent increases in plant performance. Instead, plant performance is more strongly influenced by position within the climate niche of the species, position along environmental gradients, and climatic or other differences among regions. We demonstrate that individual‐level and population‐level performance traits can yield different predictors of plant performance. Therefore, future studies comparing plant performance in native and non‐native ranges should include both plant and population characteristics and should also sample the target species from multiple regions in both ranges and along environmental gradients that comprehensively represent the niche of the species.

Bromus tectorum Response to Fire Varies with Climate Conditions - Kimberley Taylor; Tyler Brummer; Lisa J. Rew; Matt Lavin; Bruce D. Maxwell (Ecosystems, 2014)

Life after establishment: factors structuring the success of a mountain invader away from disturbed roadsides - Fredric W. Pollnac; Lisa J. Rew (Biological Invasions, 2014)

Plant invasion at landscape and local scales along roadways in the mountainous region of the Greater Yellowstone Ecosystem - Fredric Pollnac; Tim Seipel; Charles Repath; Lisa J. Rew (Biological Invasions, 2012)

Reduced Impacts or A Longer Lag Phase? Tamarix in the Northwestern U.S.A. - Erik A. Lehnhoff; Lisa J. Rew; Cathy A. Zabinski; Fabian D. Menalled (Wetlands, 2012)

Processes at multiple scales affect richness and similarity of non‐native plant species in mountains around the world - Tim Seipel; Christoph Kueffer; Lisa J. Rew; Curtis C. Daehler; Aníbal Pauchard; Bridgett J. Naylor; Jake M. Alexander; Peter J. Edwards; Catherine G. Parks; José Ramon Arevalo; Lohengrin A. Cavieres; Hansjörg Dietz; et al. (Global Ecology and Biogeography, 2012)
Aim To investigate how species richness and similarity of non‐native plants varies along gradients of elevation and human disturbance. Location Eight mountain regions on four continents and two oceanic islands. Methods We compared the distribution of non‐native plant species along roads in eight mountainous regions. Within each region, abundance of plant species was recorded at 41–84 sites along elevational gradients using 100‐m 2 plots located 0, 25 and 75 m from roadsides. We used mixed‐effects models to examine how local variation in species richness and similarity were affected by processes at three scales: among regions (global), along elevational gradients (regional) and with distance from the road (local). We used model selection and information criteria to choose best‐fit models of species richness along elevational gradients. We performed a hierarchical clustering of similarity to investigate human‐related factors and environmental filtering as potential drivers at the global scale. Results Species richness and similarity of non‐native plant species along elevational gradients were strongly influenced by factors operating at scales ranging from 100 m to 1000s of km. Non‐native species richness was highest in the New World regions, reflecting the effects of colonization from Europe. Similarity among regions was low and due mainly to certain Eurasian species, mostly native to temperate Europe, occurring in all New World regions. Elevation and distance from the road explained little of the variation in similarity. The elevational distribution of non‐native species richness varied, but was always greatest in the lower third of the range. In all regions, non‐native species richness declined away from roadsides. In three regions, this decline was steeper at higher elevations, and there was an interaction between distance and elevation. Main conclusions Because non‐native plant species are affected by processes operating at global, regional and local scales, a multi‐scale perspective is needed to understand their patterns of distribution. The processes involved include global dispersal, filtering along elevational gradients and differential establishment with distance from roadsides.

Searching for a Needle in a Haystack: Evaluating Survey Methods for Non-indigenous Plant Species - Lisa J. Rew; Bruce D. Maxwell; Frank L. Dougher; Richard Aspinall (Biological Invasions, 2006)